Pembentukan Kelas Emas (Kelurahan Antistunting Untuk Masyarakat Sehat Sejahtera) Dengan Pemanfaatan Potensi Alam Wonosalam Sebagai Pangan Bergizi Berdaya Dukung e-Complete Untuk Pencapaian SDGS - Khanifah, Farach; Sari, Evi Puspita; Srihono, Alex (Yayasan Daarul Huda Kruengmane, 2025)
Stunting is a chronic nutritional problem which is still one of the major challenges in Panglungan Village, Wonosalam District, Jombang Regency. This community service activity aims to decrease stunting rates through the formation of “Golden Classes” (Antistunting Families for a Healthy Prosperous Society) with an educational approach, health screening, and utilization of local potential in the form of turmeric, kelor, milk and chocolate as functional foods. Activities include extensions on stunting, anemia, and worms; screening hemoglobin levels in adolescents and pregnant mothers; examination of worms in toddlers; manufacturing training of processed nutritious foods (chocolate-chocolate noodles and turmeric-milk ice cream); as well as the development of e-complete educational applications. Results showed a prevalence of anemia of 42.1% in adolescents and 70% in pregnant mothers, as well as a diarrhea rate in toddlers of 26.9%. There was a significant improvement in the knowledge of the participants after the extension. Nutritious food training encourages family self-reliance in nutrition fulfillment as well as opening business opportunities. The e-complete innovation supports continuing education and monitoring of nutrition interventions. This program proves that the integration of educational approaches, technology, and local food utilization can be an effective strategy in the acceleration of stunting decline.